2020
DOI: 10.1186/s12872-020-01450-z
|View full text |Cite
|
Sign up to set email alerts
|

A model to predict unstable carotid plaques in population with high risk of stroke

Abstract: Background: Several models have been developed to predict asymptomatic carotid stenosis (ACS), however these models did not pay much attention to people with lower level of stenosis (<50% or carotid plaques, especially instable carotid plaques) who might benefit from early interventions. Here, we developed a new model to predict unstable carotid plaques through systematic screening in population with high risk of stroke. Methods: Community residents who participated the China National Stroke Screening and Prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…HDL can prevent atherosclerosis by protecting the vascular endothelium and reversing cholesterol transport function [ 31 ]. Yin et al found that low levels of HDL-C (< 1.04 mmol/L) were significantly associated with unstable carotid plaques in populations with a high risk of stroke [ 32 ]. A case‒control study involving 187 patients with severe carotid artery stenosis revealed that the LDL-C/HDL-C ratio was an independent risk factor for vulnerable plaque [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…HDL can prevent atherosclerosis by protecting the vascular endothelium and reversing cholesterol transport function [ 31 ]. Yin et al found that low levels of HDL-C (< 1.04 mmol/L) were significantly associated with unstable carotid plaques in populations with a high risk of stroke [ 32 ]. A case‒control study involving 187 patients with severe carotid artery stenosis revealed that the LDL-C/HDL-C ratio was an independent risk factor for vulnerable plaque [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was divided into two parts as follows: The investigation of risk factors related to stroke and adverse reactions to the vaccine. The survey of risk factors related to stroke was based on questionnaire of China National Stroke Screening and Prevention Project ( 20 ), which included basic demographic information (such as age, sex, education level, occupation, and marital status), lifestyle (e.g., smoking, drinking, exercise, and dietary habits), major medical history (heart disease, hypertension, diabetes, dyslipidemia, etc. ), and family history.…”
Section: Methodsmentioning
confidence: 99%